Development of Chemistry Learning Module Based on Discovery Learning on the Periodic Properties of Elements - Rezika Rezika; Gulmah Sugiharti (Universitas Negeri Medan, 2025)
21st century education requires students to develop competitive skills known as 4C skills. This study aims to: (1) determine the feasibility of the discovery learning-based module that has been developed. (2) determine the practicality of using the discovery learning-based module that has been developed. This study was conducted with a Research & Development approach using the 4D model. This study was conducted at SMAN 1 Tiganderket. The results of this study indicate that the discovery learning module that was developed obtained an average validation of materials and media of 3.2 and 3.1 (feasible) while the average teacher response was 98% and student response was 99.76% (very good). This shows that the discovery learning module on the material of periodic properties of elements that was developed is feasible and very good for use in chemistry learning in high school.